Management of advanced cholesteatoma: Madras ENT Research Foundation experience - Natarajan, Kiran; Kurkure, Rahul; ., Swathi; Shrivastava, Anubhav; Gajapathy, Sowmya; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Cholesteatoma is a common condition encountered by the otolaryngologist in the Indian subcontinent. Due to absence of pain in most patients, they may have advanced disease at presentation. Lack of awareness, long distance between the patient’s home and the treatment centre are also reasons for late presentation. Surgical management is the mainstay of treatment. The aim of this study was to retrospectively analyze the number of patients with advanced cholesteatoma, the extent of disease, and associated complications. Methods: Fifty one patients out of a total of 1132 patients with cholesteatoma presented with advanced disease in a tertiary referral centre between January 2010 to January 2020. The surgical issues in the management of the disease and the outcomes were studied. Results: Fifty one patients presented with extensive cholesteatoma in a tertiary referral centre. There were 33 males and 18 females in the study. Of fifty one patients, pediatric cholesteatoma was seen in 6 patients. Hearing loss was the most common presentation. Facial palsy, labyrinthine fistula, dural involvement, internal auditory meatus involvement was noted in some patients. All patients underwent surgical management with good outcomes. Conclusions: Advanced cholesteatoma is a dreaded disease that can result in various complications. Involvement of the facial canal, labyrinth, cochlea, dura, internal auditory meatus, internal carotid artery, jugular bulb, and sigmoid sinus involvement in the presence of extensive disease should be identified before surgery. Appropriate treatment with complete disease clearance can result in good outcomes.